PERANCANGAN PENJADWALAN PERAWATAN MESIN CHILLER DENGAN METODE RELIABILITY CENTERED MAINTENANCE (RCM) II DAN AGE REPLACEMENT DI PT. XYZ - Leslie Shofira Wijaya (2021)
This research is conducted to design a maintenance schedule for chiller machine in PT. XYZ. The purpose of this research is to obtain the right schedule for critical components of chiller machine by using Reliability Centered Maintenance II and Age Replacement Methods to reduce the breakdown, increase reliability, and have a production process with no resistance. The critical components are evaporator, condenser, distribution pump, compressor, and circulation pump because the RPN of these components are exceeding the critical RPN value. The research result using RCM II obtained inspection interval for Evaporator is 154 hours with increasing reliability to 84.6%, for Condenser is 69 hours with increasing reliability to 93.8%, for Distribution Pump is 54 hours with increasing reliability to 77.4%, for Compressor is 140 hours with increasing reliability to 99.9%, and for Circulation pump is 50 hours with increasing reliability to 99.6%. The research result using Age Replacement obtained preventive replacement interval for evaporator is 245 hours with increasing reliability to 63.4%, for Condenser is 191 hours with increasing reliability to 64.6%, for Distribution Pump is 72 hours with increasing reliability to 62.5%, for Compressor is 556 hours with increasing reliability to 92.6%, and for circulation pump is 326 hours with increasing reliability to 66.1%. The proposal given is a schedule maintenance design for 2021.